The Effectiveness of Oketani Massage on Breast Milk Volume in Postpartum Mothers - Indrayani, Triana; Andriani, Yeni (GLOBAL HEALTH SCIENCE GROUP, 2023)
Breastfeeding serves as a vital means of fostering a psychological connection between mother and baby, contributing to the attainment of Sustainable Development Goals (SDGs). One common challenge in the postpartum period is insufficient breast milk production. Oketani massage emerges as a breast care technique capable of enhancing pectoralis muscle strength to boost breast milk production. Objective: This study aimed to assess the effectiveness of Oketani massage on breast milk volume in postpartum mothers. Method: This study employed a quasi-experimental design with a before-and-after treatment approach. The sample comprises 30 mother respondents, with 15 mothers in the postpartum experimental group and 15 in the postpartum control group. Purposive sampling was utilized as the sampling technique. The instrument involved direct observation and a breast pump. Data analysis included descriptive statistics and inferential statistics, specifically paired t-test. Results: The results of this study reveal a significant different in the volume of breast milk before and after the application of Oketani massage in both the experimental and control groups. Conclusions and Recommendations: The study concludes that Oketani massage is effective in increasing breast milk volume.